Interactive 3D visualization of structural changes in the brain of a person with corticobasal syndrome - Hänel, Claudia; Pieperhoff, Peter; Hentschel, Bernd; Amunts, Katrin; Kuhlen, Torsten (Frontiers in Neuroinformatics, 2014)
The visualization of the progression of brain tissue loss, which occurs in neurodegenerative diseases like corticobasal syndrome (CBS), is an important prerequisite to understand the course and the causes of this neurodegenerative disorder. Common workflows for visual analysis are often based on single 2D sections since in 3D visualizations more internally situated structures may be occluded by structures near the surface. The reduction of dimensions from 3D to 2D allows for an holistic view onto internal and external structures, but results in a loss of spatial information. Here, we present an application with two 3D visualization designs to resolve these challenges. First, in addition to the volume changes, the semi-transparent anatomy is displayed with an anatomical section and cortical areas for spatial orientation. Second, the principle of importance-driven volume rendering is adapted to give an unrestricted line-of-sight to relevant structures by means of a frustum-like cutout. To strengthen the benefits of the 3D visualization, we decided to provide the application next to standard desktop environments in immersive virtual environments with stereoscopic viewing as well. This improves the depth perception in general and in particular for the second design. Thus, the application presented in this work allows for an easily comprehensible visual analysis of the extent of brain degeneration and the corresponding affected regions.